A standardised frankincense extract reduces disease activity in relapsing-remitting multiple sclerosis (the SABA phase IIa trial). Issue 4 (16th December 2017) - Stürner, Klarissa Hanja; Stellmann, Jan-Patrick; Dörr, Jan; Paul, Friedemann; Friede, Tim; Schammler, Sven; Reinhardt, Stefanie; Gellissen, Susanne; Weissflog, Gainet; Faizy, Tobias Djamsched; Werz, Oliver; Fleischer, Sabine; et al.
Abstract : Objective: To investigate whether oral administration of a standardised frankincense extract (SFE) is safe and reduces disease activity in patients with relapsing-remitting multiple sclerosis (RRMS). Methods: We performed an investigator-initiated, bicentric phase IIa, open-label, baseline-to-treatment pilot study with an oral SFE in patients with RRMS (NCT01450124 ). After a 4-month baseline observation phase, patients were treated for 8 months with an option to extend treatment for up to 36 months. The primary outcome measures were the number and volume of contrast-enhancing lesions (CEL) measured in MRI during the 4-month treatment period compared with the 4-month baseline period. Eighty patients were screened at two centres, 38 patients were included in the trial, 28 completed the 8-month treatment period and 18 of these participated in the extension period. Results: The SFE significantly reduced the median number of monthly CELs from 1.00 (IQR 0.75–3.38) to 0.50 (IQR 0.00–1.13; difference −0.625, 95% CI −1.25 to −0.50; P<0.0001) at months 5–8. We observed significantly less brain atrophy as assessed by parenchymal brain volume change (P=0.0081). Adverse events were generally mild (57.7%) or moderate (38.6%) and comprised mainly gastrointestinal symptoms and minor infections. Mechanistic studies showed a significant increase in regulatory CD4+ T cell markers and a significant decrease in interleukin-17A-producing CD8+ T cells indicating a distinct mechanism of action of the study drug. Interpretation: The oral SFE was safe, tolerated well and exhibited beneficial effects on RRMS disease activity warranting further investigation in a controlled phase IIb or III trial. Clinical trial registration: NCT01450124; Results.